Removal Efficiency of Chemical Oxygen Demand on Greywater using Multi Soil Layering (MSL) Technology - Syafrudin Syafrudin; Mochtar Hadiwidodo; Irawan Wisnu Wardhana; Tika Ayu Kusuma Wardani; Indah Sekar Arumdani; Sudarno Sudarno; Nurandani Hardyanti (Universitas Diponegoro, 2021)
Greywater is household waste sourced from kitchens and bathrooms, except for toilets. Around 58%-85% of greywater can be generated from the total volume of household wastewater per house. It is necessary to treat wastewater before it is discharged into water bodies to prevent the adverse effects of contaminants on the environment and human health while reducing the demand for clean water. However, due to environmentally friendly, socially sustainable, and economical treatment costs, considering that greywater is produced every day and continuously, Multi Soil Layering (MSL) technology can be an alternative to remove contaminants in water. Thus, this study aims to determine the migration of COD in greywater using MSL technology. Other parameters tested were pH and temperature by taking samples of wastewater in residential areas of Semarang City. In this study, there are two stages, namely the preliminary stage and the running stage. The MSL system will use three reactors with andosol soil, apus bamboo, and coconut shell activated charcoal as mixed soil blocks (SMB). Reactor A (activated charcoal and andosol soil), reactor B (bamboo apus and andosol soil), reactor C (andosol soil, bamboo apus, activated charcoal). The results of domestic wastewater treatment using the MSL method in each of the three reactors could remove COD by 75%, 74%, and 76%. Reactor C obtained the highest COD removal efficiency compared to other reactors.